Preparation Junctions for All-Ceramic CAD/CAM Crown and Bridge Restorations - Vlahova Angelina (Balkan Stomatological Society, 2016)
Background: The preparation junction type is determined by a number of factors that need to be taken in consideration with CAD/CAM Fixed Prosthodontics: the used material; the condition of the retainer teeth, their periodontium and the occlusion; the design software and the type of drills; the working protocol; the cement and the method of cementation.